Vaginal Microbiota Changes in Patients With Premature Ovarian Insufficiency and Its Correlation With Ovarian Function - Wen, Jingyi; Feng, Yanzhi; Yan, Wei; Yuan, Suzhen; Zhang, Jinjin; Luo, Aiyue; Wang, Shixuan (Frontiers in Endocrinology, 2022)
Objectives To reveal the characteristics of vaginal microbiota in premature ovarian insufficiency (POI) patients and their relationship with ovarian function. Materials and Methods In this case-control study, the vaginal bacterial composition of 30 POI patients and 26 healthy women of comparable age was assessed by 16S rRNA gene sequencing targeting the V3-V4 hypervariable regions. The metabolic functions of vaginal microflora were preliminarily predicted through the PICRUSt2 analysis. Redundancy analysis and Spearman’s correlation analyzed the relationships between vaginal microbiota and ovarian function indicators. Results Actinobacteria, Atopobium, and Gardnerella were significantly increased in POI patients. Their increments were significantly negatively correlated with anti-müllerian hormone (AMH) and inhibin B, and positively correlated with follicle-stimulating hormone (FSH) and luteinizing hormone (LH). While Bifidobacterium was significantly decreased in POI patients. Its relative abundance was significantly positively correlated with AMH and negatively correlated with FSH and LH. Then, POI patients included in this study were divided into POI (25 < FSH ≤ 40) (n = 9) and premature ovarian failure (POF) (FSH > 40) (n = 21) subgroups according to serum FSH levels. Compared with the controls, Firmicutes and Lactobacillus were significantly decreased only in POF (FSH > 40) patients, while no difference was observed in POI (25 < FSH ≤ 40) patients. Lactobacillus was negatively correlated with FSH. Firmicutes was significantly reduced and Actinobacteria was significantly increased in POF (FSH > 40) patients compared with POI (25 < FSH ≤ 40) patients. The key bacterial taxa Gardnerella and Atopobium showed potency in predicting POI. Conclusions Here we demonstrated significant changes in the vaginal microbiota of POI patients, and these changes were significantly correlated with reduced ovarian reserve, endocrine disruption, and symptoms of perimenopausal syndrome. Differences in vaginal microbiota between POI (25 < FSH ≤ 40) and POF (FSH > 40) patients were also identified. These findings may provide new evidence for the relationship between vaginal microbiota and ovarian function.